2022
DOI: 10.1007/s10072-022-05972-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive telemedicine solution for remote monitoring of Parkinson’s disease patients with orthostatic hypotension during COVID-19 pandemic

Abstract: Objective Orthostatic hypotension (OH) represents a frequent but under-recognized phenomenon in Parkinson’s disease (PD). During COVID-19 pandemic, Information and Communication Technologies (ICT) have become pivotal in the management of chronic diseases like PD, not only to assess motor impairment, but also for vital signs monitoring. This pilot study aimed to propose a real-time remote home-monitoring system and protocol for PD patients with OH. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Indeed, although such technology might have some limitations in providing an assessment of core body temperature during exercise and its precision should be further evaluated [37][38][39], it might be useful for detecting hyperthermic events in the clinical setting, particularly when compared to other non-invasive methods which might not provide continuous temperature readings [40][41][42] or when patients have to be remotely monitored [1,[43][44][45][46]. Our results showed that a novel non-invasive wireless heat flux-based thermometer was able to detect body temperature changes measured by the tympanic thermometer as the presence or absence of hyperthermia (94.1%) and the presence or absence of fever (97.4%) in the post-stroke clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although such technology might have some limitations in providing an assessment of core body temperature during exercise and its precision should be further evaluated [37][38][39], it might be useful for detecting hyperthermic events in the clinical setting, particularly when compared to other non-invasive methods which might not provide continuous temperature readings [40][41][42] or when patients have to be remotely monitored [1,[43][44][45][46]. Our results showed that a novel non-invasive wireless heat flux-based thermometer was able to detect body temperature changes measured by the tympanic thermometer as the presence or absence of hyperthermia (94.1%) and the presence or absence of fever (97.4%) in the post-stroke clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…13 Research on home-monitoring systems to help evaluate movement disorders remotely is also being actively conducted. 14 In our survey, 93.4% of participants responded that they were in favor of introducing telemedicine for parkinsonian disorders. While telephone consultations and prescriptions were temporarily permitted during the COVID-19 outbreak, additional discussions are needed to establish the scope and methodology of the introduction of telemedicine in Korea.…”
mentioning
confidence: 83%
“…A total of 77.5% of respondents said that they offered phone counseling to patients during the pandemic and that this option was “broadly accepted” by patients [ 13 ]. Research on home-monitoring systems to help evaluate movement disorders remotely is also being actively conducted [ 14 ]. In our survey, 93.4% of participants responded that they were in favor of introducing telemedicine for parkinsonian disorders.…”
mentioning
confidence: 99%
“…On the other hand, supine hypertension may occur [ 10 ] because the baroreflex and renal mechanisms are not centrally coordinated to respond to fluid from the lower extremities returning to central compartments overnight. There is also marked variability in systolic BP [ 37 , 38 , 39 ], which is frequently elevated in the morning. Capturing these features requires frequent BP measures with morning measurements or measurements when at least one stressor, for example, standing, is present.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement is often prompted by a history of symptoms consistent with OH. However, history is unreliable, with episodes of OH frequently asymptomatic or unrecognised by the PwP [ 4 , 37 , 40 ], as well as the presence of symptoms not correlating with the presence of OH [ 37 ]. Furthermore, as discussed above, OH can be intermittent and thus missed by a single measurement, which also cannot identify variability or morning supine hypertension.…”
Section: Introductionmentioning
confidence: 99%